INCIDENCIA DE LA EVALIACION Y CONTROL EN LA PREVENCION DE LAS ENFERMEDADES INFECTOCONTAGIUOSAS EN NIÑOS MENORES DE CINCO AÑOS, DEL CENTRO DE SALUD NO 8, DEL AREA NO 4 PARROQUIA FEBRES CORDERO DE LA CIUDAD DE GUAYAQUIL, EN LA PROVINCIA DEL GUAYAS. - FELIPE MUÑOZ LEON (2012)
INCIDENCE OF EVALUATION AND CONTROL IN THE PREVENTION OF INFECTOCONTAGIOUS DISEASES IN CHILDREN UNDER FIVE YEARS OF AGE, AT HEALTH CENTER NO 8, AREA NO 4 FEBRES CORDERO PARISH IN THE CITY OF GUAYAQUIL, IN THE PROVINCE OF GUAYAS.